Bridging Policy and Public: Stakeholder Engagement Strategy in Indonesia's Ministry of Finance - Zulfiningrum, Rahmawati; Indrayani, Heni; Aditia, Nico; Harriadi, Ibrahim; Sumartias, Suwandi; Jaya, Joana (Nyimak: Journal of Communication, 2025)
In the era of information transparency and rising public expectations, governmental institution face challenges not only in disseminating information but also in cultivating lasting stakeholder relationships. The Ministry of Finance of the Republic of Indonesia, as the principal administrator of fiscal policy, must manage fiscal communication in a way that balances efficiency with inclusivity. This study examines the Ministry's communication strategy for engaging both internal and external stakeholders. Employing Stakeholder Engagement theory, a qualitative methodology, and a case study approach, data were gathered via in-depth interviews with six heads of Sub-Division from the Bureau of Communication and Information Services, Ministry of Finance. Research indicates that stakeholder engagement techniques concentrate on four approaches: dialogue, information distribution, message transmission, and broadcasting. Internal elements, including motivation, authority, and organizational dynamics, affect communication efficacy. Stakeholder mapping, communication strategy, and risk management are essential in the external setting. These practices demonstrate how internal organizational capacity and external stakeholder dynamics jointly influence engagement outcomes, including legitimacy, participation, and collaborative value creation. The primary contribution of this study is the development of a conceptual model that explains the mechanisms linking internal organizational factors to external stakeholder engagement. This model offers a comprehensive understanding of how state institutions can transform communication into participatory and accountable governance. It emphasizes the significance of transformative communication in promoting participatory, inclusive, transparent, and responsive governance that aligns with public needs. Keywords: External communication, internal communication, public participation, stakeholder engagement, strategic communication ABSTRAKDi era transparansi informasi dan meningkatnya ekspektasi publik, lembaga pemerintah menghadapi tantangan tidak hanya dalam menyebarkan informasi tetapi juga dalam membangun hubungan pemangku kepentingan yang berkelanjutan. Kementerian Keuangan Republik Indonesia, sebagai administrator utama kebijakan fiskal, harus mengelola komunikasi fiskal dengan menyeimbangkan efisiensi dan inklusivitas. Penelitian ini mengkaji strategi komunikasi Kementerian dalam melibatkan pemangku kepentingan internal dan eksternal. Dengan menggunakan teori Stakeholder Engagement, metodologi kualitatif, dan pendekatan studi kasus, data diperoleh melalui wawancara mendalam dengan enam kepala Sub Bagian dari Biro Komunikasi dan Layanan Informasi Kementerian Keuangan. Hasil penelitian menunjukkan bahwa teknik keterlibatan pemangku kepentingan berpusat pada empat pendekatan: dialog, distribusi informasi, penyampaian pesan, dan penyiaran. Faktor internal termasuk motivasi, otoritas, dan dinamika organisasi yang mempengaruhi efektivitas komunikasi, sedangkan proses eksternal seperti pemetaan pemangku kepentingan, perancangan strategi, dan manajemen risiko menjadi landasan operasional. Praktik-praktik ini menunjukkan bagaimana kapasitas organisasi internal dan dinamika pemangku kepentingan eksternal secara bersama-sama membentuk hasil keterlibatan, seperti legitimasi, partisipasi, dan penciptaan nilai kolaboratif. Kontribusi utama penelitian ini adalah pengembangan model konseptual yang menjelaskan mekanisme yang menghubungkan faktor internal organisasi dengan keterlibatan pemangku kepentingan eksternal. Model ini menawarkan pemahaman komprehensif tentang bagaimana lembaga negara dapat mengubah komunikasi menjadi tata kelola yang partisipatif dan akuntabel. Penelitian ini menekankan pentingnya komunikasi transformatif dalam mendorong tata kelola yang partisipatif, inklusif, transparan, dan responsif sesuai dengan kebutuhan publik.Kata Kunci: Komunikasi eksternal, komunikasi internal, komunikasi strategis, partisipasi publik, stakeholder engagement